Correlation of Serum Calcium with the Severity of Acute Ischemic Stroke Patients Presenting at Tertiary Care Hospital, Karachi: Serum Calcium with the Severity of Acute Ischemic Stroke Patients - Hyder, Fezan; Kumari, Monika; Ali, Syed Gohar; Syed, Mohsina; Javed, Ahsan; Anwar, Wajeeha (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
Stroke is a significant chronic illness, death and disability in both developed and developing nations. The interrelation between the level of serum calcium and the processes of ischemic injury is not clear. Objectives: To identify the relationship between the level of serum calcium and the extent of acute ischemic stroke behavior in patients who reported to a tertiary care hospital in Karachi. Methods: The cross-sectional analytic study was done in the Neurology Department of Civil Hospital, Karachi. A total of 138 patients diagnosed with acute ischemic stroke, fulfilling the diagnostic criteria, were included after obtaining verbal consent. Serum calcium levels were measured within 24 hours of admission. Simple descriptive statistics (mean ± SD) were used for quantitative data, while qualitative variables were given in terms of frequencies and percentages. A p-value of less than 0.05 was taken as statistically significant. Results: Among 138 patients, the mean age was 51.14 ± 4.49 years, and the mean calcium level was 10.7 ± 1.32 mg/dl. Based on calcium quartiles, 28 (20.3%), 35 (25.4%), 54 (39.1%), and 21 (15.2%) patients fell into quartiles 1, 2, 3, and 4, respectively. Stroke severity (based on NIHSS scores) distribution was: mild (15.2%), moderate (29.7%), moderate to severe (20.3%), and severe (34.8%). Higher calcium levels were positively correlated with increased stroke severity (p≤0.05). Conclusions: Serum calcium levels measured within 24–48 hours of admission showed a strong correlation with both stroke severity and functional outcome. Therefore, calcium levels may serve as an indicator of disease severity in acute ischemic stroke patients.